PENERAPAN PRINSIP PACTA SUN SERVANDA DALAM KASUS PELANGGARAN HAM PADA KEBIJAKAN OPEN THE GATE POLICYMILIK JERMAN - Oktaviasari, Awanda Cindy; Saleh, Mohammad (Jurnal HUKUM BISNIS, 2025)
ABSTRACT This study examines the application of the pacta sunt servanda principle in the context of Germany’s Open the Gate Policy as a response to the Syrian refugee crisis. The pacta sunt servanda principle obliges states to honor international agreements they have ratified, including the 1951 Refugee Convention and various European Union regulations such as the Lisbon Treaty and the Dublin Regulation. In practice, Germany initially became one of the most open countries to refugees; however, this policy triggered serious challenges, including allegations of human rights violations in refugee camps and procedural inconsistencies with international standards. This research employs a normative juridical method with statutory and historical approaches. The findings indicate that although Germany adhered to international agreements at the outset, it faced legal and reputational consequences due to inadequate human rights protections in implementation. The study recommends the importance of aligning domestic policies with international obligations to prevent violations against refugees and asylum seekers. Furthermore, the active involvement of international institutions such as the UNHCR is essential in monitoring the enforcement of human rights principles at the global level. Keywords: Pacta Sunt Servanda, Open the Gate Policy, Germany, Syrian Refugees, Human Rights Violations, International Law